Energy endowment, energy capacity aggregation and carbon emissions in china-empirical analysis based on spatial durbin model - Wang, Guoyu; Zhou, Jinsheng (Frontiers in Environmental Science, 2022)
This paper investigates how regional energy endowment affects carbon emissions and whether energy capacity aggregation plays a mediating role. In the context of the "double carbon target", it is important to study the relationship between energy endowment and carbon emission growth to formulate reasonable and effective energy policies in the region. Based on the panel data of 30 Chinese provinces from 2008-2019, this paper investigates the mechanism of the role between energy endowment, energy capacity aggregation, and carbon emissions using the spatial Durbin model. The results show that: (1) Carbon dioxide emissions have significant positive spatial autocorrelation. (2) Energy endowment and energy capacity aggregation increase provincial carbon emissions. For each unit increase in energy endowment and energy capacity aggregation level, regional carbon emissions will increase by 0.0423 units and 0.0564 units. Moreover, the effect of energy endowment on carbon emissions has a spatial spillover effect. (3) The intermediary effect test finds that energy capacity aggregation plays an intermediary role in the energy endowment affecting carbon emissions. Therefore, this paper verifies that energy endowments promote regional carbon emissions and that the energy capacity aggregation effect plays a mediating role. The research results provide theoretical guidance for solving the contradictory problem of energy demand growth on carbon emission limitation and promoting regional green and low-carbon development.